Essays on demographic and health economics - Szklo, Michel (2022)
This thesis consists of three papers on demographic and health economics. The first chapter documents trends in life expectancy inequality across Brazilian states. We apply demographic methods to estimate the main determinants of the slowdown of the convergence process. Our analysis suggests that young adult and mid-aged mortality and mortality due to external causes are the main drivers of that process, with elderly mortality gaining importance in the last years. The second chapter, a joint work with Damian Clarke and Rudi Rocha, treats Brazil as a case study to document the causal effects of health spending on infant mortality. By leveraging the variation in health spending promoted by Brazil's 29th Constitutional Amendment of 2000, we are able to document not only the effects of health spending on infant mortality, but also the links in the chain connecting spending to health outcomes. We show that increases in health spending translate into greater primary care coverage, higher supply of hospitals and low skilled professionals. We then document moderate reductions in infant mortality within 24 hours and due to perinatal conditions, as well as long term reductions in total infant mortality, infant mortality amenable to primary care, and infant mortality by infectious and respiratory causes. Our results contribute to the literature on the impacts of health spending by providing one of the first causal parameters of the relationship between spending and health outcomes. Lastly, the third chapter combines health economics with political economy to describe the relationship between term limits and opportunistic political business cycles in public health care, and to document the electoral returns of public health spending at the local level. By leveraging the variation in health spending promoted by Brazil's 29th Constitutional Amendment of 2000 we are able to describe differential increases in spending, types of spending and health inputs, between municipalities with mayors in first and second mandates. Moreover, we take advantage of this exogenous variation to estimate the electoral returns to health spending. Our results suggest that term limits lead to opportunistic behavior and that voters reward increases in health spending. The estimates suggest that this effect is mediated by increases in primary care coverage and the supply of hospitals.